Weeneebayko Area Health Authority-ICES-Laurentian University Collaboration: Working together to support communities with Indigenous Health Research in the James and Hudson Bay Region, in Northeast Ontario, Canada. - Beth Rachlis; Kathleen Qu; Justice Seidel; Yantao Zhao; Robert Gagnon; Sandra Kioke; Elaine Innes; Minnie Ho; Charles Victor; Sujitha Ratnasingham; Jennifer D. Walker; Loretta Loon (International Journal of Population Data Science, 2022)
Objective The James and Hudson Bay Region, consisting of six remote Indigenous communities, have experienced barriers accessing regional health data. To inform local health planning, the Minomathasowin Healthy Living department in the Weeneebayko Area Health Authority (WAHA), ICES and Laurentian University developed a Collaboration, to co-create enhanced Indigenous data stewardship.